The effect of principals’ transformational leadership and organizational culture on teacher performance - Setya Raharja; Irdayanti Mat Nashir; Dwi Esti Andriani (Jurnal Kependidikan Penelitian Inovasi Pembelajaran, 2022)
This study aimed to examine the effect of the principals’ transformational leadership and organizational culture on teacher performance in the Indonesian context. The research instrument used was a closed-ended questionnaire which the validity was measured by the content validity by means of expert judgment. The population of this study was 343 JHS teachers in Bantul. A sample of 164 teachers was selected by means of the proportional stratified sampling technique. The valid questionnaire was then tested on 30 junior high school teachers. Instrument reliability testing was performed by statistical analysis using Cronbach’s alpha. The results show that the teacher performance is inclined by the principal transformational leadership and organizational culture both separately and simultaneously. An organizational culture has a greater effect than principal transformational leadership on teacher performance. It also shows that teacher performance is influenced by other factors. It suggests that school principals should develop a strong organizational culture and practice transformational leadership.